Comparative study of laparoscopic and conventional (Lichtenstein tension free) inguinal hernia repair in a tertiary care institute - Dhawan, Nitish; Goyal, Kirti Savyasacchi; Sodhi, Tejinder Pal Singh; Chaudhary, Manu (International Surgery Journal, 2019)
Background: Inguinal hernia repair is the most frequently performed operation in general surgery. The standard method for inguinal hernia repair had changed little over a hundred years. Methods: Present study was conducted on 60 patients having inguinal hernia and were operated by two different methods i.e. Lichtenstein tension free inguinal hernia repair (Group A) and laparoscopic hernia repair (Group B). Aim of the study conducted was to compare the various observations and complications in post-operative period. Results: There was no statistically significant difference in the age group, side and type of hernia in the two groups. Laparoscopic repair was a longer procedure than Lichtenstein inguinal hernia repair and it was statistically significant (p<0.05). Postoperatively urinary retention was the most common complication in Group A. Other complications were genital oedema (13.33%), haematoma (13.33%), seroma (13.33%) and wound infection (6.67%) which led to increased post-operative hospital stay. In Group B, pneumoscrotum was the most common complication. Other complications included subcutaneous emphysema (6.67%) and seroma (6.67%). Conclusions: Lichtenstein tension free inguinal hernia repair is safe, efficient and cheaper procedure with no extra equipment being required while Laparoscopic repair takes more time, laparoscopic equipment and training in minimal access surgery.